Young patients and gastrointestinal (GI) tract malignancies - are we addressing the unmet needs?. Issue 1 (December 2016) - Perl, G.; Nordheimer, S.; Lando, S.; Benedict, C.; Brenner, B.; Perry, S.; Shmoisman, G.; Purim, O.; Amit, L.; Stemmer, S.; Ben-Aharon, I.
Abstract Background Recent epidemiological studies indicate the rate of gastrointestinal (GI) malignancies among younger patients is increasing, mainly due to colorectal cancer. There is a paucity of data regarding the magnitude of treatment-related symptoms, psychosocial issues and potential unmet needs in this population. We aimed to characterize the needs of this population to evaluate whether unmet needs could be targeted by potential intervention. Methods Female and male patients diagnosed with cancer of the gastrointestinal tract <40y retrospectively completed a questionnaire to evaluate symptoms, daily function and unmet needs at pre-treatment, during and post-treatment. Comparisons were made by gender, disease stage and treatment modality. Multiple linear regression models evaluated effects of demographics, symptoms and needs on multiple domains of health-related-quality-of-life (using Short-Form Health Survey-12 and CARES). Results Fifty patients were enrolled (52 % female) to a pilot study. Median age at diagnosis was 35.5y (range, 21-40y). The symptoms that significantly increased from baseline to during and post-treatment were: diarrhea (37 %), sleeping disorder (32 %) and sexual dysfunction (40 %). Patients also reported significant deterioration in occupational activities and coping with children compared with baseline. Female patients reported significant unmet need for nutritional counseling and psychosocial support compared to male patients (p  < 0.05). Patients treated with multimodality-treatment presented higher rates of unmet needs (p  = 0.03). Conclusions Young patients with GI cancers represent a group with unique characteristics and needs compared with published evidence on other young-onset malignancies. The distinctive symptoms and areas of treatment-related functional impairments indicate there are unmet needs, especially in the area of psychosocial support and nutritional counseling.